Literatur Review: Transparansi Dan Akuntabilitas Dalam Administrasi Publik Di Kota Merauke - Natalia Suryani Purba (Jurnal Impresi Indonesia, 2025)
This article aims to explain the concepts of transparency and accountability in public administration, particularly in Merauke City, an autonomous region in eastern Indonesia. Through a desk-based approach, this study examines basic theories, local policy practices, and implementation challenges in the digital era. Merauke, as a border city, has both potential and challenges in implementing the principles of good governance. This study shows that although e-Government policies have begun to be implemented, obstacles remain in terms of digital literacy, infrastructure, and public participation. The results of this study are expected to encourage the government and the community to work together to create good governance, in this case in the city of Merauke.